Exposure to environmental tobacco smoke among South Korean adults: a cross-sectional study of the 2005 Korea National Health and Nutrition Examination Survey - Ha Eun-Hee; Lee Bo-Eun (BMC, 2011)
Abstract Background Studies have identified that environmental tobacco smoke exposure is associated with sociodemographic factors such as age, sex, and socioeconomic status, but few studies have been conducted in South Korea. In this study, the authors investigated the extent of environmental tobacco smoke exposure and factors related in a nationally representative sample of Korean adults. Methods The data of 7,801 adults aged 19 years and over collected during the 2005 Korea National Health and Nutrition Examination Survey were analyzed. Information on smoking habits and exposure to environmental tobacco smoke was obtained by self-reports using a standardized questionnaire. Risks of environmental tobacco smoke exposure conferred by sociodemographic variables and behavioral risk factors were evaluated using logistic regression methods. Results Overall, 36.1% of nonsmokers (defined as those not currently smoking) and 50.1% of current smokers were found to be exposed to environmental tobacco smoke either at work or at home. Among the nonsmokers, women were more likely to be exposed to environmental tobacco smoke at home (OR = 5.22, 95%CI, 4.08-6.67). Furthermore, an inverse relationship was found between education level and the risk of environmental tobacco smoke exposure at home (OR = 1.73, 95%CI, 1.38-2.17 for those with a high school education; OR = 2.30, 95%CI, 1.68-3.16 for those with a middle school education; and OR = 2.58, 95%CI, 1.85-3.59 for those with less than an elementary school education vs. those with a college education or more). In addition, those with office, sales service, or manual labor jobs were found to be at significantly higher risk of environmental tobacco smoke exposure at work than those with professional, administrative, or managerial jobs. Also, the risk of environmental tobacco smoke exposure in the workplace was significantly higher for alcohol drinkers than non-drinkers (OR = 1.23, 95%CI, 1.07-1.47). After adjusting for age, sex and education, it was found that those exposed to environmental tobacco smoke at home were more likely to have been admitted to hospital during the previous year (OR 1.29, 95%CI, 1.002-1.66). Conclusions In this study of Korean adults, exposure to environmental tobacco smoke at home or work was found to be affected by sex, age, marital status, educational level, and type of occupation. Accordingly, these factors should be given appropriate consideration by those developing policies or interventions designed to control exposure to environmental tobacco smoke.